Percutaneous Mechanical Atherectomy Plus Thrombectomy Using the Rotarex®S Device Followed by a Drug-Coated Balloon for the Treatment of Femoropopliteal Artery In-stent Restenosis: A Prospective Single-Center, Single-Arm Efficacy Trial (PERMIT-ISR Trial) - Liu, Ming-Yuan; Li, Wenrui; Guo, Xiaobo; Zhang, Zhiwen; Liu, Bin; Yu, Hongzhi; Zhang, Zhe; Chen, Xueming; Feng, Hai (Frontiers in Surgery, 2021)
Background: Studies investigating debulking devices with drug-coated balloons (DCBs) in the treatment of femoropopliteal (FP) artery in-stent restenosis (ISR) are limited. We aimed to evaluate the safety and midterm outcome of percutaneous mechanical atherectomy plus thrombectomy (MATH) using the Rotarex®S (Straub Medical, Wangs, Switzerland) catheter followed by a DCB in the treatment of FP-ISR. Methods: This study was a single-center single-arm trial. Patients with symptomatic (Rutherford category 2–5) de novo restenosis lesions of FP-ISR were treated with MATH and subsequent DCB. From June 2016 to May 2018, 59 patients with FP-ISR were enrolled. The primary endpoint was target lesion revascularization (TLR) and changes in the Rutherford category of the target limb at 12 months. Secondary endpoints included primary and secondary patency at 12 months, technical success rate, major adverse events, and ankle-brachial index (ABI). Risk factors for TLR were analyzed using Cox proportional hazard model. Results: The average follow-up time was 33 ± 8 months. The rate of technical success was 88.1% (52/59). Nine patients received bailout stenting. The rate of freedom from TLR was 84.7% (50/59) at 1 year, the Rutherford category changed at 12 months were significantly improved from baseline (p < 0.01). The primary patency rates and the secondary patency at the 12-month follow-ups were 82.5 and 92.5%, respectively. The ABI changed at 12 months were significantly improved from baseline (p < 0.01). Global limb anatomic staging system (GLASS) classification III [hazard ratio (HR) 18.44, 95% CI (1.57–215.99), p = 0.020] and postoperative Rutherford classification ≥4 [HR 8.28, 95% CI (1.85–37.06), p = 0.006] were identified as independent predictors of TLR. Conclusion: Our preliminary data suggested that MATH using a Rotarex®S catheter combined with DCB angioplasty is a safe, minimally invasive, and effective treatment for FP-ISR with favorable, immediate, and midterm outcomes. Clinical Trial Registration:http://www.chictr.org.cn, identifier [ChiCTR2000041380].